2019
DOI: 10.3390/toxins11060310
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Azoxystrobin on Mycotoxins and Related Fungi in Italian Paddy Rice

Abstract: The efficacy of azoxystrobin was evaluated in the presence of mycotoxigenic fungi and relative mycotoxins in Italian paddy rice during the growing season in the field. Three experimental fields were considered and the applied experimental design was a strip plot with three replicates; rice samples were collected at four different growing stages. The efficacy of the fungicide treatment on rice fungal population was demonstrated with around 20% less total fungal incidence in sprayed samples compared to untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Rice variety is relevant for fungal contamination, with Sole CL having the highest presence of fungi and CL26 the highest contamination with Aspergillus species (p ≤ 0.01) (Table 1). These data confirm results obtained in our previous studies where Sole CL was found to be the most contaminated rice variety and CL26 the most susceptible rice variety to A. versicolor infection [8,9]. 1).…”
Section: Fungal Incidence and Mycotoxin Contaminationsupporting
confidence: 92%
See 3 more Smart Citations
“…Rice variety is relevant for fungal contamination, with Sole CL having the highest presence of fungi and CL26 the highest contamination with Aspergillus species (p ≤ 0.01) (Table 1). These data confirm results obtained in our previous studies where Sole CL was found to be the most contaminated rice variety and CL26 the most susceptible rice variety to A. versicolor infection [8,9]. 1).…”
Section: Fungal Incidence and Mycotoxin Contaminationsupporting
confidence: 92%
“…Contamination by STC is low and not statistically different for the two years considered (Table 1). The rice variety showing the highest contamination by STC is Sole CL (Table 1), confirming data also found in our previous studies where this variety seemed to be more susceptible to STC accumulation [8,9] even if it showed a low Aspergillus spp. incidence.…”
Section: Fungal Incidence and Mycotoxin Contaminationsupporting
confidence: 90%
See 2 more Smart Citations
“…The reduction of mycotoxin contamination can be obtained by intervening during the cultivation or storage of products. Research carried out by Giorni et al [ 8 ] tested the efficacy of the fungicide azoxystrobin on fungal parasites of rice and obtained a strong reduction (−67%) of sterigmatocystin while deoxynivalenol remained unaffected.…”
mentioning
confidence: 99%